Hello World! Third Edition - Sande, Warren; Sande, Carter (Manning Publications, 2019)
Hello World! Computer Programming for Kids and Other Beginners, Third Edition introduces the world of computer programming in a clear and fun style. Using Python, a programming language designed to be easy to learn, each engaging lesson teaches skills that apply to any kind of programming. It brings to life the basic concepts of computing-looping, decisions, input and output, graphics, and more. Written by father-and-son team Warren and Carter Sande, this international bestseller is kid-tested and reviewed by professional educators. Now in its third edition, Hello World! has been fully updated to Python 3 and includes a new chapter about how the internet works.